THE SURVIVAL OF THE NATIONAL INSTITUTE OF LIBRARY AND INFORMATION SCIENCES IN A TURBULENT PUBLIC UNIVERSITY - Wijetunge, Pradeepa (Malaysian Journal of Library and Information Science, 2003)
The public university system of Sri Lanka faces a number of difficulties. The National Institute of Library and Information Sciences (NILIS) was established affiliated to a university with World Bank aid. However NILIS had to face several problems at the inception and it was almost closed down. The author describes the threats encountered by LIS schools in other countries and the strategies at the macro and micro level, adopted especially by the developed countries, to survive and develop. She further explains different strategies adopted for the survival of NILIS. Expansion in participation with other departments and expansion alone using a variety of innovations take prominence here.